TEACHING AUTHENTIC TEXTS OF LINGUOCULTURAL CONTENT AT THE INITIAL STAGE OF TEACHING A FOREIGN LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Students' ability to engage in independent speaking activities is closely linked to their interest and motivation in learning a foreign language. Studies show that learners, regardless of age, are especially drawn to the cultures and lifestyles of countries where the target language is spoken. This engagement creates significant opportunities to enhance the quality of language education and communication exercises. This article explores the significance of incorporating authentic teaching materials, with a particular focus on their role in reading instruction for foreign language learners